2018
DOI: 10.1155/2018/9281946
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics Study Based on LC‐MS and Antihypertensive Effect of Uncaria on Spontaneously Hypertensive Rats

Abstract: Our previous studies have shown that Uncaria has an important role in lowering blood pressure, but its intervention mechanism has not been clarified completely in the metabolic level. Therefore, in this study, a combination method of HPLC-TOF/MS-based metabolomics and multivariate statistical analyses was employed to explore the mechanism and evaluate the antihypertensive effect of Uncaria. Serum samples were analyzed and identified by HPLC-TOF/MS, while the acquired data was further processed by partial least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Several biomarkers were previously found in a metabolomics study by this research group. These biomarkers were mainly associated with lipid, vitamin and amino acid metabolism [2,3]. However, in these experimental studies of hypertension, changes in metabolites were measured at one time point, and dynamic monitoring was not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Several biomarkers were previously found in a metabolomics study by this research group. These biomarkers were mainly associated with lipid, vitamin and amino acid metabolism [2,3]. However, in these experimental studies of hypertension, changes in metabolites were measured at one time point, and dynamic monitoring was not performed.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrodia elata can antagonize epinephrine, regulate blood vessels, and dilate small blood vessels, thereby regulating blood pressure. In addition, several clinical studies found that Uncaria could decrease BP effectively by regulating the above biomarkers and metabolic pathways [47]. e antihypertensive effect of Uncaria alkaloids is related to the decrease in frequency [48].…”
Section: Discussionmentioning
confidence: 99%
“…CerS form dihydroceramides by condensing sphinganine and acyl-CoA, and they are a family of six isoforms (CerS1-6) that each display specificity for certain acyl-CoA chain lengths. Ceramides are formed from dihydroceramides by the action of the enzyme dihydroceramide desaturase ( 41 , 42 ).…”
Section: Introduction To Ceramidesmentioning
confidence: 99%
“…Both dihydroceramides and ceramides correlate with the release of the inflammatory cytokine interleukin 6 (IL-6), but only dihydroceramides correlates with macrophage inflammatory protein 1β (MIP-1β) release ( 13 , 15 ). Studies have also shown that dihydroceramide levels are elevated in patients with rheumatoid arthritis ( 109 ), patients with left ventricular assist devices ( 110 ) and hypertensive rats ( 13 15 , 41 , 111 , 112 ).…”
Section: Introduction To Ceramidesmentioning
confidence: 99%